(untitled) (American Journal of Islam and Society, 2022)
Since the beginning of the twentieth century, modernist Islamic reformers have proposed more “objectives of Islamic law” or maqāṣid al-sharī‘ah and argued that the maqāṣid-oriented approach indicates that Islamic priorities include the modern principles of democracy, social justice, human rights, and government accountability. This paper considers the evolution of maqāṣid and its relationship with the traditional framework of uṣūl al-fiqh. Subsequently, it addresses how the new maqāṣid discourse has been politicized. It analyzes the use of maqāṣid by Shaykh ‘Abdullah Bin Bayyah in his recent declarations concerning the UAE’s policies against regional democracy. This paper argues that Bin Bayyah’s interpretation of maṣlaḥah (legal benefit) and his adoption of the idea of absolute obedience to the ruler (walī al-amr) are not based on the traditional interpretation of the sacred texts that have been adopted by Salafists and Traditionalists. Rather, it is deeply rooted in the maqāṣid discourse and rational reasoning related to Islamic modernism. The article includes a comprehensive examination of Bin Bayyah’s justifications, as based on two basic points: first, the priority of peace as a higher objective (maqṣid) of sharī‘ah than rights and justice; second, the verification of the ratio legis (taḥqīq al-manāṭ). This paper argues that this ideological interpretation could shift the purpose-0riented basis of maqāṣid al-sharī‘ah to result-oriented objectives, which focus on specific ideologies to satisfy contradicting political ends.